Pollen in Polar Ice Implies Eastern Canadian Forest Dynamics Diverged From Climate After European Settlement - Sandra O. Brugger; Nathan J. Chellman; Andreas Plach; Paul D. Henne; Andreas Stohl; Joseph R. McConnell (Geophysical Research Letters)
Abstract Rapid warming and human exploitation threaten boreal forests. Understanding links among vegetation, climate, and people in this vast biome requires highly resolved long‐term records that integrate regional inputs. We developed an 850‐year pollen‐based record of supraregional vegetation change using a southern Greenland ice core and atmospheric modeling that identified the boreal and mixed‐conifer forests of eastern Canada as the dominant pollen source regions. Conifer pollen increased ∼1400 CE at the onset of the cooler and drier Little Ice Age. A subsequent decline began ∼1650 CE and a statistically significant pollen change after 1760 CE suggests ecological consequences of the Little Ice Age cooling and initial human exploitation that persisted until recent decades. These supraregional changes are broadly consistent with local records and demonstrate intensification of human impacts on northern forests, suggesting a shift from a climate‐modulated to an increasingly human‐controlled system during recent centuries.